(3GdBdI hGdYed aj GdeLJeY GdHOhj (B:s (3OQGSI aj GdCfJQhHhdhLjG GdEbJUGOjI (B/s - (3YHS, eMeO jSQi GHQGgjes ((3GdEScfOQjI(B: s (3OGQ GdeYGQa(B, s, 1996)
(3GdYdGbI Hjf GdBdI aj GdeLJeY GdHOhj(B- (3GdBdI hGSJKeGQ GdehGQO aj GdeLJeY GdHOhjs
Keywords: (3GdBdIs; (3GdCfJQhHhdhLjG GdEbJUGOjIs; (3GdYeds